URGENSI PERLINDUNGANDATA PRIVASIDALAM ERA EKONOMI DIGITAL DI INDONESIA - Dewi Rosadi, Sinta; Gumelar Pratama, Garry (Veritas et Justitia, 2018)
As a prerequisite to enter into the digital economic system, the government should be able to guarantee and secure public trust in online transactions and communications.  At the same time the need arise to secure and protect privacy and personal data. The author, utilizing a juridical normative or dogmatic approach,discusses the issue how the Indonesian government should provide better and more reliable protection of privacy and personal data. Notwithstanding the existence of a number of rules from different Acts which provides for such protection, these are considered not sufficient in providing certainty in the digital era. The authors main argument is that a legal instrument providing privacy and personal data protection should fulfil three criteria: (1) possessing international character; (2) protecting privacy and personal data as a positive right; and (3) function to co-relate individual to the economic community as such.